ANALISIS PENGARUH PEMBIAYAAN MUDHARABAH, MUSYARAKAH DAN MURABAHAH TERHADAP RETURN ON EQUITY BANK UMUM SYARIAH - AISYAH .; Jaryono .; Sulistyandari . (Jurnal Ekonomi Dan Bisnis, 2017)
This research is a descriptive research by using the quantitative approach that is conducted atIslamic Banks which is listed in Financial Service Authority (OJK). This research entitles: “The Analysis of the Financing Effect of Mudharabah, Musyarakah, and Murabahah to the Return On Equity of Islamic Banks”. The purpose of research is to find out the effect of funding of mudharabah,  musyarakah, and murabahah to the Return On Equity. Population in this research is Islamic Banks that is listed in Financial Service Authority (OJK) in period 2010-2014. Purposive sampling method in this research is used to determine the sample that is applied in this research. After purposive s ampling, there is just 8 banks from 12 total islami c banks that are listed in Financial Service Authority (OJK) which fulfills the criteria to be used as sample. Based on the result of research and data analysis use the double linear regression (supported with software analysis of SPSS 21 for Windows) shows that: (1) Financing of Mudharabah gives the positive and significant effect to the Return On Equity (ROE) of Islamic Banks in Indonesia, (2) Financing of Musyarakah does not give effect to the Return On Equity (ROE) of Islamic Banks in Indonesia, (3) Financing of Murabahah does not give the effect to the Return On Equity (ROE) of Islamic Banks in Indonesia.   Implication from the conclusion above that Islamic Banks is would be better to increase the financing of mudharabah because it gives the bigger benefit for islamic bank. To increase the financing of musyarakah by giving financing to the construction projects and infrastructures because it will get the bigger benefit for islamic banks. To increase the financing of islamic banks is suggested to do the stages as following: routine controlling to the funding, policy management of financing implementation, to be more selective in selecting the candidate of financing. Bank also must be discipline for its employees in the field of appraisal of the candidate of customer. Key words : Mudharabah financing, Musyarakah financing, Murabahah financing, and Return on equity(ROE)